Impact of nurse-mediated management on achieving blood pressure goal levels in primary care: Insights from the Valsartan Intensified Primary carE Reduction of Blood Pressure Study. (1st October 2016) - Carrington, Melinda J; Jennings, Garry L; Harris, Mark; Nelson, Mark; Schlaich, Markus; Stocks, Nigel P; Burrell, Louise M; Amerena, John; de Looze, Ferdinandus J; Swemmer, Carla H; Kurstjens, Nicol P; Stewart, Simon; et al.
Abstract: Background: Blood pressure targets in individuals treated for hypertension in primary care remain difficult to attain. Aims: To assess the role of practice nurses in facilitating intensive and structured management to achieve ideal BP levels. Methods: We analysed outcome data from the Valsartan Intensified Primary carE Reduction of Blood Pressure Study. Patients were randomly allocated (2:1) to the study intervention or usual care. Within both groups, a practice nurse mediated the management of blood pressure for 439 patients with endpoint blood pressure data ( n =1492). Patient management was categorised as: standard usual care ( n =348, 23.3%); practice nurse-mediated usual care ( n =156, 10.5%); standard intervention ( n =705, 47.3%) and practice nurse-mediated intervention ( n =283, 19.0%). Blood pressure goal attainment at 26-week follow-up was then compared. Results: Mean age was 59.3±12.0 years and 62% were men. Baseline blood pressure was similar in practice nurse-mediated (usual care or intervention) and standard care management patients (150 ± 16/88 ± 11 vs . 150 ± 17/89 ± 11 mmHg, respectively). Practice nurse-mediated patients had a stricter blood pressure goal of ⩽125/75 mmHg (33.7% vs . 27.3%, p =0.026). Practice nurse-mediated intervention patients achieved the greatest blood pressure falls and the highest level of blood pressure goal attainment (39.2%) compared with standard intervention (35.0%), practice nurse-mediated usual care (32.1%) and standard usual care (25.3%; p <0.001). Practice nurse-mediated intervention patients were almost two-fold more likely to achieve their blood pressure goal compared with standard usual care patients (adjusted odds ratio 1.92, 95% confidence interval 1.32 to 2.78; p =0.001). Conclusion: There is greater potential to achieve blood pressure targets in primary care with practice nurse-mediated hypertension management.